Perfluorooctane sulfonate (PFOS), a novel environmental pollutant, induces liver injury in mice by activating hepatocyte ferroptosis - Yang Yang; Liuwei Xie; Yu Zhu; Yongjia Sheng; Jin Wang; Xiaohong Zhou; Wenyan Li; Chenxi Cao; Yi Yang; Chenyang Han (Ecotoxicology and Environmental Safety, 2023)
Objective: We investigated the toxicological mechanism by which perfluorooctane sulfonate (PFOS) induces liver injury via ferroptosis. Methods: Primary mouse hepatocytes were treated with LD50 = 55 M PFOS. Their cytotoxicity was detected by CCK-8 and LDH assays, while JC-1 staining was used to identify their mitochondrial membrane potential. GSH-Px, MDA, and SOD levels were determined using kits, and Fe2 + levels were determined using the FerroOrange probe and iron ion assay kit. The DCFH-DA probe was used to examine ROS levels, while Western blot was used to examine protein expressions. After treatment with the ferroptosis inhibitor YL939 and the ROS inhibitor BABTA, the ability of PFOS to induce ferroptosis was observed. In animal experiments, we examined the liver function and the degree of hepatic ferroptosis of mice treated with PFOS as well as their histopathological changes. Results: PFOS could induce hepatocyte ferroptosis, while YL939 and BABTA treatment could inhibit PFOS-induced ferroptosis. PFOS could induce liver injury and increase ferroptosis levels in tissue, while treatment with YL939 and BABTA could inhibit liver injury. Conclusion: PFOS can induce ferroptosis in hepatocytes and cause liver injury in mice, which is its toxicological mechanism.